RESEARCH ON SOME ASPECTS OF POULTRY MEAT QUALITY DEPENDING ON STORAGE - Rita GOLBAN; Artur GOLBAN; Aurel CIUCLEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study of current research is of interest regarding the assessment of the quality of poultry meat depending on the storage conditions. The scientific researches were performed using the following research methods: microscopic visualization, bacterioscopic and bacteriological methods qualitative and quantitative analysis, induction, deduction, the graphics method, the chronological series method. The results of the researches on the quality of poultry meat assortments demonstrated aspects of the quality of poultry meat assortments after 24 hours of refrigeration with a higher weight in the sample of poultry meat of the assortment purchased from the market - 3 isolated bacterial colonies, followed by the poultry meat of domestic origin-2 colonies and bacterial colony determined in store-bought poultry meat depending on various storage conditions. In the scientific research are analyzed the consumption of meat by different categories, the origin of poultry meat sold on markets from Moldova, the analysis of quality based on storage and proposed recommendations related the improving the quality of the poultry meat.